2016
DOI: 10.1186/s12944-016-0384-3
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between serum apolipoprotein M levels and hepatitis B virus DNA load in HBeAg-negative chronic hepatitis B

Abstract: BackgroundHepatitis virus B (HBV) has infected millions of people worldwide. Notably, such infections can be associated with hepatic complications. Levels of apolipoprotein M (apoM), a component of high-density lipoprotein (HDL), are known to be significantly elevated in patients with chronic hepatitis B (CHB). The aim of this study was to investigate the relationship between HBV DNA load in serum and serum apoM levels in patients with CHB.MethodsA total of 73 HBeAg-negative CHB patients, 50 HBeAg-positive CHB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Hepatocytes are the major sites of apolipoprotein synthesis and lipoprotein assembly, secretion, uptake, and catabolism. Some clinical studies in HBV-infected population have found significantly decreased levels of plasma ApoA1 (Jiang et al, 2014;Wang Y. et al, 2016;Cui et al, 2019), ApoA5 (Zhu et al, 2016;Cui et al, 2019), ApoB (Wang et al, 2011;Cui et al, 2019), and ApoC3 (Zhu et al, 2017;Cui et al, 2019), whereas dramatically increased level of serum ApoM or ApoE (Gu et al, 2011;Shen et al, 2016). These results from clinical studies were consistent with observations from several experimental studies.…”
Section: The Effect Of Hbv On Apolipoprotein Metabolism In Hepatocytessupporting
confidence: 87%
See 1 more Smart Citation
“…Hepatocytes are the major sites of apolipoprotein synthesis and lipoprotein assembly, secretion, uptake, and catabolism. Some clinical studies in HBV-infected population have found significantly decreased levels of plasma ApoA1 (Jiang et al, 2014;Wang Y. et al, 2016;Cui et al, 2019), ApoA5 (Zhu et al, 2016;Cui et al, 2019), ApoB (Wang et al, 2011;Cui et al, 2019), and ApoC3 (Zhu et al, 2017;Cui et al, 2019), whereas dramatically increased level of serum ApoM or ApoE (Gu et al, 2011;Shen et al, 2016). These results from clinical studies were consistent with observations from several experimental studies.…”
Section: The Effect Of Hbv On Apolipoprotein Metabolism In Hepatocytessupporting
confidence: 87%
“…While expression of ApoE ( Shen et al, 2015 ) or ApoM ( Gu et al, 2011 ) increased after HBV infection. Changes in hepatic lipid metabolism induced changed lipid levels in peripheral blood, including increased SFA and MUFA ( Arain et al, 2018 ), decreased ApoA1, ApoA5, ApoB100, or ApoC3 ( Wang et al, 2011 ; Jiang et al, 2014 ; Wang Y. et al, 2016 ; Zhu et al, 2016 , 2017 ; Cui et al, 2019 ), or increased ApoE or ApoM ( Gu et al, 2011 ; Shen et al, 2016 ). However, the level of TG and TC showed a decrease in CHB patients compared to normal controls ( Wong et al, 2012 ; Cheng et al, 2013 ; Joo et al, 2017 ).…”
Section: The Effect Of Hbv On Apolipoprotein Metabolism In Hepatocytementioning
confidence: 99%
“…It was reported that HBV down-regulated the expression of ApoA1, ApoA5, ApoB and up-regulated the expression of ApoM [ 8 11 ].The main purpose of this study is to investigate the effect of HBV on the regulation of ApoC3 expression and its mechanism by in vivo and in vitro experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In plasma, apoM is transported with HDL, and apoM + HDL accounts for 5% of the total HDL. Recently, the antiinflammatory functions of apoM, mediated by HDL, have attracted increasing attention (11)(12)(13)(14). The ApoM gene is on chromosome 6 and located close to inflammatory genes, including TNF-α and TNF-β (8).…”
Section: Introductionmentioning
confidence: 99%